Early sex detection and physiological stimulation of spawning in the Mozambique tilapia Oreochromis mossambicus (Peters, 1852) - Izhboldina, O. O.; Izhboldina, O.; Izhboldina, Е. А.; Izhboldina, Н.; Izhboldina, Е.; Izhboldina, Olena; Іжболдіна, Олена Олександрівна; Pishchan, I. S.; Pishchan, Ilona; Pischan, I. S.; Pischan, E.; Піщан, Ілона Станіславівна; et al. (My University, 2019)
The article presents the results of an experimental study on physiological stimulation of tilapia spawning and methods of early sex detection in juvenile fish. It has been determined that among organic dyes, solution of diamond green has shown the best results in determining the sex of juvenile tilapia. It has been found that the pituitary gland of carp is suitable for stimulation of reproductive products maturation in tilapia and causes spawning behavior in fish. Under controlled conditions, this allows obtaining a constant number of larvae of a certain age and size, which is an essential prerequisite for industrial fish breeding technology. У статті представлені результати експериментального дослідження фізіологічної стимуляції нересту тилапії та методів раннього виявлення статі у молодняку. Визначено, що серед органічних барвників розчин алмазного зеленого показав найкращі результати при визначенні статі неповнолітніх тилапії. Встановлено, що гіпофіз коропа підходить для стимуляції дозрівання репродуктивних продуктів у тилапії та спричиняє нерестові риби у риб. У контрольованих умовах це дозволяє отримати постійну кількість личинок певного віку та розміру, що є важливою умовою технології промислового розведення риби.
Раннє виявлення статі та фізіологічна стимуляція нересту в мозамбіковій тилапії Oreochromis mossambicus (Peters, 1852)
Іжболдіна Олена Олександрівна https://orcid.org/0000-0002-8816-2228 Піщан Ілона Станіславівна https://orcid.org/0000-0001-5030-6348 Храмкова Ольга Миколаївна http://orcid.org/0000-0002-0697-7715 Милостивий Роман Васильович https://orcid.org/0000-0002-4450-8813
Keywords: aquatic bioresources; водні біоресурси; aquaculture; аквакультура; fish; риба; tilapia; тилапія; reproduction; відтворення; hydrobionts; гідробіонти